Macroeconomics Determinants Of External Debt In Malaysia - Evan, Lau; Syn-Yee, Alvina Lee; Mohammad Affendy, Arip (The International Institute of Social and Economic Sciences, 2015)
The management of debt has always been one of the central concerns in the small open economy like Malaysia. This study seeks to re-examine whether the macroeconomic indicators contributed to the external debt in Malaysia. Utilizing Malaysia data from 1970 to 2013, the results indicate the existence of short run causality linkages between the external debt and the macroeconomic indicators. Further dynamic analysis indicates that real interest rate (RIR) to be the most exogenous variable beyond the sample for the next 50 years. This implies that policymakers could focus on the monetary variables in assisting and managing external debt level in the long run. Malaysia should develop a debt governance program for pursuit of debt-targeting policies or rules to enhance sound public finance systems which is crucial for Malaysia to achieve solvency in external debt positions in the near future.